2020
DOI: 10.3126/kumj.v18i2.32958
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Dental Problems among Patients Visiting a Dental Hospital during COVID-19 Pandemic

Abstract: Background Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Nepal is a part of this worldwide corona virus disease. In this critical situation, the patients have a sense of insecurity visiting dental hospital. Objective To assess the pattern of dental problems in patients visiting a dental college during COVID-19. Method A descriptive cross-sectional study was conducted in Dental Hospital of Kathmandu Medical College and Teaching Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
1
Order By: Relevance
“…10,14,[20][21][22][23][24] But other studies showed contrary to the present study. 6,7,11,18,19,[25][26][27] In this study, the most common oro-dental disease among male was dental caries 2,448(33.87%) followed by gingivitis/periodontitis 2403(33.25%) whereas the most common oro-dental disease in female was gingivitis/periodontitis 2,673(30.89%), followed by dental caries 2580(33.25%). Similar to the present study, a study done at a pediatric hospital in Bangladesh showed more males presented with caries (54.68%) than females (45.32%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…10,14,[20][21][22][23][24] But other studies showed contrary to the present study. 6,7,11,18,19,[25][26][27] In this study, the most common oro-dental disease among male was dental caries 2,448(33.87%) followed by gingivitis/periodontitis 2403(33.25%) whereas the most common oro-dental disease in female was gingivitis/periodontitis 2,673(30.89%), followed by dental caries 2580(33.25%). Similar to the present study, a study done at a pediatric hospital in Bangladesh showed more males presented with caries (54.68%) than females (45.32%).…”
Section: Discussionmentioning
confidence: 53%
“…6 A study done in Nepal showed that the major dental problems in patients were dental pain and swelling requiring endodontic consultation. 7 Oral health is essential to general health. 8 Thus, the objective of the study was to find out the oro-dental disease pattern of patients, which has been recorded at the dental department of Patan Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was little variation in the gender distribution, a slight decrease in the proportion of females and an increase among male patients was also witnessed in China [ 5 ] and Saudi Arabia [ 8 ]. Increased dental-related emergencies were also observed in Nepal [ 9 ] with reports of increased reliance on pharmaceutical management of dental conditions in Australia [ 10 ].…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 99%
“…Most studies concluded that there was an increase in the provision and utilisation of emergency oral health services [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. The key reasons for emergency visits included trauma, acute pulpitis, acute periodontitis and plaque-induced gingivitis/oral mucosal conditions [44,59].…”
Section: Provision and Utilisation Of Emergency Oral Health Servicesmentioning
confidence: 99%